Consumers' Willingness to Pay for Sustainable Seafood Made in Europe. Issue 3 (3rd July 2018) - Zander, Katrin; Feucht, Yvonne
ABSTRACT: Sustainability of increasing relevance also for seafood markets. The aim of this contribution is to analyze consumer preferences and their willingness to pay (WTP) for different sustainability claims, and to identify consumer segments according to their WTP. The contingent valuation method was applied to elicit consumers' WTP in eight European countries. The WTP varies between seven and almost 20%, depending on attribute and country. Three consumer groups become apparent: the largest group without any additional WTP, a smaller group with a moderate additional WTP of plus 17%, and a very small group with an additional WTP of more than 40%. Clear differences between countries are obvious regarding preferences for different sustainability attributes, particularly in the segment with the highest WTP. A fraction of the consumers is willing to pay significantly higher prices for sustainably produced fish from Europe: given that trustful standards are applied and well communicated.